Clinical advances in obsessive-compulsive disorder: a position statement by the International College of Obsessive-Compulsive Spectrum Disorders. (July 2020) - Fineberg, Naomi A.; Hollander, Eric; Pallanti, Stefano; Walitza, Susanne; Grünblatt, Edna; Dell'Osso, Bernardo Maria; Albert, Umberto; Geller, Daniel A.; Brakoulias, Vlasios; Janardhan Reddy, Y.C.; Arumugham, Shyam Sundar; Shavitt, Roseli G.; et al.
Abstract : In this position statement, developed by The International College of Obsessive-Compulsive Spectrum Disorders, a group of international experts responds to recent developments in the evidence-based management of obsessive-compulsive disorder (OCD). The article presents those selected therapeutic advances judged to be of utmost relevance to the treatment of OCD, based on new and emerging evidence from clinical and translational science. Areas covered include refinement in the methods of clinical assessment, the importance of early intervention based on new staging models and the need to provide sustained well-being involving effective relapse prevention. The relative benefits of psychological, pharmacological and somatic treatments are reviewed and novel treatment strategies for difficult to treat OCD, including neurostimulation, as well as new areas for research such as problematic internet use, novel digital interventions, immunological therapies, pharmacogenetics and novel forms of psychotherapy are discussed.